Ionothermal Synthesis of Lanthanide Tetrafluoride Nanoparticles Using Deep Eutectic Solvents. Issue 1804 (2015) - Furman, Benjamin R.; Gutierrez, Robert D.; Baker, Charles K.
ABSTRACT: We have developed a new method for controlling the size, crystallinity, and polydispersity of 100–2000 nm tetrafluoride phosphor particles. Five polyol-based deep eutectic solvents (DESs) were downselected out of a set of more than 130 candidates. We analyzed their benefits in synthesizing phosphor matrix particles of β -NaYF4, β -NaYbF4, and β -NaGdF4 . We produced green (λmax = 540 nm) and blue/UV (λmax = 450 nm) upconverting phosphors in DES using Yb, Er and Yb, Tm codopants, respectively. The blue/UV phosphor reaction was scaled the up to 25 L, yielding nearly 400 g of high-quality, bright photoluminescent, β -phase product under mild conditions. We conclude that polyol-based DES systems offer a uniquely specialized and useful toolkit for phosphor synthesis.